'A Call to Women', 1947 (pg. 3) (1947)
1947 1945-1960 "'A Call to Women', 1947 (pg. 3)" [hfr0172c], 1947 This press notice from the Ministry of Labour and National Service in June 1947 launches a campaign to encourage women back into work to combat the post war economic crisis and labour shortage.